Lightsheet fluorescence lifetime imaging microscopy with wide‐field time‐correlated single photon counting. Issue 2 (25th November 2019) - Hirvonen, Liisa M.; Nedbal, Jakub; Almutairi, Norah; Phillips, Thomas A.; Becker, Wolfgang; Conneely, Thomas; Milnes, James; Cox, Susan; Stürzenbaum, Stephen; Suhling, Klaus
Abstract: We report on wide‐field time‐correlated single photon counting (TCSPC)‐based fluorescence lifetime imaging microscopy (FLIM) with lightsheet illumination. A pulsed diode laser is used for excitation, and a crossed delay line anode image intensifier, effectively a single‐photon sensitive camera, is used to record the position and arrival time of the photons with picosecond time resolution, combining low illumination intensity of microwatts with wide‐field data collection. We pair this detector with the lightsheet illumination technique, and apply it to 3D FLIM imaging of dye gradients in human cancer cell spheroids, and C. elegans . Abstract : We combine fluorescence lifetime imaging (FLIM) with lightsheet illumination microscopy for 3D imaging of human cancer cell spheroids and living C. elegans . The wide‐field TCSPC method used for FLIM detection has many advantages including extremely low illumination intensity, good signal‐to‐noise ratio and insensitivity to intensity fluctuations and photobleaching, while lightsheet illumination provides optical sectioning, making this technique ideal for 3D FLIM imaging of living organelles.